Experiential knowledge transmission - Conjard, Patrick; Saint-Genis, Emmanuelle (Arbetsmarknad & Arbetsliv, 2018)
This paper addresses the question of experiential knowledge transfer. It shows that “training” responses in companies need to be designed with the stakeholders, looking as closely as possible at the work activity and the actual conditions required to successfully carry out the complex activities in which experiential learning is put to work. After setting out the focus of the research – experiential knowledge transfer – and providing some theoretical background information, this paper gives recommendations to companies or consultants wishing to better address this issue and improve their practices.